Macroremain counts from borehole Sokli B series in Sokli (Finland) in 2002 - Karin Helmens; Jonas Bergman; Stefan Engels; Päivi Kaislahti; Shyhrete Shala; Minna Väliranta (PANGAEA, 2025)
This dataset provides absolute counts of botanical and zoological macro-remains obtained from the Early Weichselian sediment sequence retrieved from Sokli (Finland) in 2002. Counts per taxon are presented against sediment depth (m), and the volume of sediment used for each sample (ml^3) is provided to allow the calculation of concentrations. For some taxa relative counts (Rel) are presented where: Rel.1 = Rare, less than 5 occurrences; Rel.2 = regular-mass occurrences. The macroremain dataset consists of a total of 90 samples and provides information on terrestrial and aquatic ecosystem dynamics (Helmens et al., 2012) and was used to reconstruct climate conditions (Väliranta et al., 2009). Macrofossil samples were prepared from subsamples of mainly ca. 10 ml^3. The sediment was sieved using a 100 μm mesh under running water and the residue examined using stereo and high-magnification light microscopes. The volume of the sediment used for plant-macrofossil analysis was determined by displacement of water. It varied between 5 and 15 cm^3 but was typically 10 cm^3. The sediment was soaked in Na4P2O7.H2O (sodium pyrophosphate) solution to aid sediment disintegration. The sediment was sieved through a 100 um mesh and the residue was systematically examined at 10 magnification using a stereo-microscope. Critical identifications were made using a high-magnification light microscope. The analyses were performed in the laboratories of Stockholm University, Sweden.